RAPD markers in the discrimination of genetic variability in ornamental peppers - Pereira dos santos Rodrigues, Cristine Agrine; Monteiro do Rêgo, Mailson; dos Santos Pessoa, Angela Maria; da Silva Sousa, Elisandra; Ramalho do Rêgo, Elizanilda (Comunicata Scientiae, 2022)
Genetic variability in pepper genotypes has been widely assessed using phenotypic traits and molecular markers, which are essential to estimate the genetic divergence of the species and thus recommend parental individuals for breeding programs. In this scenario, this study aimed to evaluate the genetic divergence between ornamental pepper accessions (C. annuum L.) using RAPD molecular markers. Seventeen ornamental pepper accessions and one plant of the commercial cultivar Calypso were used in the study. The accessions were subjected to RAPD analysis with 15 primers. The analysis revealed high variability between the accessions and evidenced that accessions UFPB-355 and UFPB-348 were the most dissimilar, whereas accessions UFPB- 443 and UFPB-77.3 were the most similar. The accessions were grouped into three different groups, evidencing their genetic divergence The accessions characterized in this study are promising and can be used in future pepper breeding programs due to their high genetic variability. Moreover, the results obtained in this study allow recommending accessions UFPB-45, UFPB-77.3, UFPB-137, UFPB-356, and UFPB- 443 as parent individuals since they are the most divergent. Finally, the RAPD markers were highly sensitive in driscriminating pepper accessions and should be used as an auxiliary tool for choosing parents.r a divergência genética na espécie e recomendar indivíduos parentais para programas de melhoramento. Assim, este trabalho teve como objetivo avaliar a divergência genética entre acessos de pimenta ornamental ( C. annuumL.) usando marcadores moleculares RAPD. Foram utilizados 17 acessos de pimenta ornamental e uma planta da cultivar comercial Calypso. Os acessos foram submetidos à análise de RAPD, com 15 primers. A análise revelou grande variabilidade entre os acessos. Os resultados evidenciaram que os acessos UFPB-355 e UFPB-348 são os mais dissimilares, enquanto os acessos UFPB-443 e UFPB-77.3 são os mais semelhantes. Os acessos foram agrupados em três grupos, evidenciando a divergência genética entre eles. Os acessos caracterizados neste estudo são promissores e podem ser utilizados em futuros programas de melhoramento de pimenta devido à alta variabilidade genética detectada. Os resultados obtidos neste estudo permitiram indicar, como indivíduos parentais, os acessos UFPB-45, UFPB-77.3, UFPB-137, UFPB-356 e UFPB-443,